2018
DOI: 10.1080/02770903.2018.1514048
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the uses, needs, and preferences for health technology use in adolescents with asthma

Abstract: Adolescents and parents experience a number of challenges related to managing asthma, and health technology interventions should focus on ways to improve adherence and self-management. Future research considerations and potential interventions including ways to integrate adolescent preferences with evidence-based interventions are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…For this initial pilot study, we provided mobile devices to ensure that the patient's experience with the Propeller Health devices was consistent, but future studies should examine the generalizability of this type of study when using participants’ own smartphones as operating systems, phone models, and data plans can vary. Previous national and local surveys of a similar cohort of children in the Cincinnati inner‐city area showed 95% of these children have access to their own smartphones . Although automated, passive data collection from electronic inhaler monitors without requiring an open application on a smart device would be the preferred method, there is no current technology available commercially with that capability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this initial pilot study, we provided mobile devices to ensure that the patient's experience with the Propeller Health devices was consistent, but future studies should examine the generalizability of this type of study when using participants’ own smartphones as operating systems, phone models, and data plans can vary. Previous national and local surveys of a similar cohort of children in the Cincinnati inner‐city area showed 95% of these children have access to their own smartphones . Although automated, passive data collection from electronic inhaler monitors without requiring an open application on a smart device would be the preferred method, there is no current technology available commercially with that capability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous national and local surveys of a similar cohort of children in the Cincinnati inner-city area showed 95% of these children have access to their own smartphones. 44,45 Although automated, passive data collection from electronic inhaler monitors without requiring an open application on a smart device would be the preferred method, there is no current technology available commercially with that capability.…”
Section: Considerations For Future Study Designsmentioning
confidence: 99%
“…Many mHealth apps support patients with AR via self-monitoring through an electronic diary (e-Diary), personalized feedback and/or patient education (42). They aim to improve patient education and selfmanagement on a daily basis but require an evidence-based evaluation given that the information provided on the app stores is limited, in particular for the apps' validity (43)(44)(45). This can be done by evaluating the effectiveness of the app with the patients' clinical outcomes (13,28,46).…”
Section: B Apps Including Health Datamentioning
confidence: 99%
“…The emergency asthma plan is often poorly understood, reviewed sporadically and poorly implemented. The incorporation of this into an app was rated highly in Burbank's adolescent study, with 93% reporting that they would adhere better to plans accessed via an app (83) whilst Odom showed that they are easier to follow (84) and Ramsey that they are preferable to a written plan (85).…”
Section: Appsmentioning
confidence: 99%